Description of Sheep Production System, Husbandry Practices and Assessment of Major Constraint in Dawuro Zone and Konta Special Wereda of South Region of Ethiopia (Global Journal of Science Frontier Research, 2015)
The study was conducted to describe sheep husbandry practices and production system and to assess major constraint in Dawuro zone and Konta special woreda of South Nations Nationalities and Peoples Regional State of Ethiopia. A total of 180 households were selected purposively for characterization of the production system. Sampling frame was established in a multistage clustered sampling procedure in compliance with the main indigenous sheep types of the study area. A structured questionnaire, group discussion and secondary sources were used to gather data on sheep production system and husbandry practices. The result showed that most of the households heads are males (83.3%-96.7%) and mixed crop-livestock system are the dominant production system. Among the livestock species, sheep accounted for the largest proportion (35.9%-50.2%) in the study area, and the average sheep flock size ranged from 9.72 in Mareka to 11.35 in Tocha.
Keywords: description; production system; husbandry practices; constraint; dawuro; konta